A Single-Plasmid Genome Editing System for Metabolic Engineering of Lactobacillus casei - Xin, Yongping; Guo, Tingting; Mu, Yingli; Kong, Jian (Frontiers in Microbiology, 2018)
Genome engineering of Lactobacillus casei, an important industrial microorganism for dairy fermented product, currently relies on inefficient and time-consuming double crossover events. In this study, we developed an easy-to-use genome engineering strategy for metabolic engineering of L. casei for acetoin production. Plasmid pMSP456-Cre, that contains prophage recombinase operon LCABL_13040-50-60 driven by the nisin-controlled inducible expression (NICE) system and the site-specific recombinase gene cre under the control of the promoter of the lactose operon from L. casei, was constructed. Using this plasmid, integration of a hicD3 gene linear donor cassette (up-lox66-cat-lox71-down) was catalyzed by the LCABL_13040-50-60 recombinase with an efficiency of 100% and the cat gene was excised by the Cre/lox system with an efficiency of 60%. To demonstrate this system for sequential and iterative knocking out genes in L. casei, another three genes (pflB, ldh and pdhC) related to acetoin production were deleted with the efficiencies of 60%, 40% and 60%, respectively. The yielding quadruple mutant could produce a ~18-fold higher amount of acetoin than the wild-type and converted 59.8% of glucose to acetoin in aerobic. Therefore, these results proved this simple genome engineering strategy have potential in metabolic engineering of L. casei for production of high value-added metabolites.